Mode of Delivery in Premature Neonates: Does It Matter? - Diana A. Racusin; Kathleen M. Antony; Jennifer Haase; Melissa Bondy; Kjersti M. Aagaard (American Journal of Perinatology Reports, 2016)
Abstract